Pengaruh Konflik Terhadap Stres Kerja dan Kepuasan Kerja Karyawan - Han, Che; Ketut Netra, I Gusti Salit (E-Jurnal Manajemen, 2014)
This study aims to determine the effect of the conflict on job stress, the effect of the conflict on employee job satisfaction and job stress influence on job satisfaction of employees at PT Bank Rakyat Indonesia Branch Office Gajah Mada Denpasar . The type of data used is quantitative and qualitative data by source and use primary and secondary data. A total of 105 employees serve as the respondents in this study. A nalysis of the data using confirmatory factor analysis, analysis of Structural Equation Modeling and evaluation of SEM assumptions. Based on the results of the discussion, the conclusion obtained that: conflict positive effect on job stress, conflict negatively affect the employee job satisfaction, job stress and negatively affect job satisfaction of employees at PT Bank Rakyat Indonesia Branch Office Gajah Mada Denpasar . Keywords: job satisfaction, conflict, work stress Normal 0 false false false EN-US X-NONE X-NONE